Regenerative Medicine - A Future Medicine - S. S. GEDAM; H. V. SHAHARE (International Journal of Pharma and Bio Sciences, 2010)
Regenerative Medicine is the process of creating living, functional tissues to repair or replace tissue or organ function lost due to age, disease, damage, or congenital defects. Regenerative medicine also empowers scientists to grow tissues and organs in the laboratory and safely implant them when the body cannot heal itself. Importantly, regenerative medicine has the potential to solve the problem of the shortage of organs available for donation compared to the number of patients that require life-saving organ transplantation, as well as solve the problem of organ transplant rejection, since the organ’s cells will match that of the patient. It refers to a group of biomedical approaches to clinical therapies that may involve the use of stem cells. Examples include; the injection of stem cells or progenitor cells (cell therapies); another the induction of regeneration by biologically active molecules; and a third is transplantation of in vitro grown organs and tissues (Tissue engineering).